Rainwater in Egypt: quantity, distribution and harvesting - ABDEL-SHAFY, H.I.; EL-SAHARTY, A.A.; REGELSBERGER, M.; PLATZER, C. (Mediterranean Marine Science, 2010)
Egypt has limited water resources, and it will be under water stress within the year 2030. Therefore, Egypt should consider the natural and non-conventional water resources to overcome such problem. Rain harvesting is one solution; but not all; particularly on the north coast by the Mediterranean Sea and the Red sea. In this paper, the rainwater issue is reviewed and discussed in terms of the quantities and distribution at different selected areas in Egypt. The amount of rain falls at different location in Egypt was collected for a period of 16 months. The data indicated that rainfall in Egypt is very scarce, with an annual average of 12 mm and ranges from 0 mm/year in the desert to 200 mm/year in the north coastal region. The maximum total amount of rain does not exceed 1.8 billion m3per year. However, the average annual amount of rainfall water that is effectively utilized for agriculture purposes is estimated to be 1 billion m3. Harvesting pilot plant was constructed and implemented in Alexandria directly on the Mediterranean Sea. The harvested rain was used for irrigation and treated for drinking. It was, therefore, recommended to develop sustainable catchments at appropriate locations in the rain-fed areas at the north coast as well as cost effective grafting of the indigenous technologies with the innovative techniques.